1978
DOI: 10.1093/jnci/60.4.819
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-Specific Nitrosamines: Formation From Nicotine In Vitro and During Tobacco Curing and Carcinogenicity in Strain A Mice 2 3

Abstract: The formation of tobacco-specific nitrosamines from the major tobacco alkaloid nicotine was examined. Detached leaf tobacco was fed either [2'-14C]nicotine or [2'-14C]nornicotine and air cured. The cured leaf was then analyzed for [2'-14C]N'-nitrosonornicotine ([2'-14C]NNN). The yield of [2'-14C]NNN was 0.007% from nornicotine and 0.009% from nicotine. Because the ratio of nicotine to nornicotine in conventional nicotine-type tobacco is 20-100:1, nicotine is considered to be the major precursor for the carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(65 citation statements)
references
References 0 publications
1
63
1
Order By: Relevance
“…This observation can be explained by similarities in tobacco processing and is in agreement with the general principle that yields of tobacco-specific nitrosamines are influenced greatly by the processes involved in the manufacturing of smokeless tobaccos. 12,[21][22][23] The highest levels of tobacco-specific nitrosamines were observed in 2 different brands of the same variety, khaini. Khaini is a mixture of tobacco, lime and menthol or aromatic spices.…”
Section: Discussionmentioning
confidence: 99%
“…This observation can be explained by similarities in tobacco processing and is in agreement with the general principle that yields of tobacco-specific nitrosamines are influenced greatly by the processes involved in the manufacturing of smokeless tobaccos. 12,[21][22][23] The highest levels of tobacco-specific nitrosamines were observed in 2 different brands of the same variety, khaini. Khaini is a mixture of tobacco, lime and menthol or aromatic spices.…”
Section: Discussionmentioning
confidence: 99%
“…VC is a synthetic mouse lung carcinogen; AFB1 is fungal toxin and human carcinogen; NNK is a human lung carcinogen. Previous studies have demonstrated that each is a potent inducer of LAC in mice (22)(23)(24). Tumors were induced with 20 or 60 mg VC/kg body weight by a single intraperitoneal (i.p.)…”
Section: Lung Tumors and Cell Linesmentioning
confidence: 99%
“…Nicotine, nornicotine, anabasine, and anatabine are precursors of TSNAs in tobacco and tobacco smoke (205,206). Both nicotine and nornicotine are considered to be NNN precursors.…”
Section: Tsnas In Mss: Direct Transfer From Tobacco and Conflicting Dmentioning
confidence: 99%